Dukungan Keluarga Dan Kepatuhan Pengobatan Penderita Tuberkulosis Paru Di Sentani, Papua - Tuturop, Katarina Lodia; Yufuai, Agustina Regina (Madu : Jurnal Kesehatan, 2025)
Treatment adherence is a major challenge in controlling Pulmonary Tuberculosis (TB). Family support is believed to be a key factor, yet the specific roles of different support dimensions within unique socio-economic contexts like Papua are not well understood. The aim of this study is to analyze the relationship between family support dimensions and medication adherence among Pulmonary TB patients in the working area of Sentani Kota Health Center. This study employed an analytical survey design with a cross-sectional approach. The sample consisted of 79 Pulmonary TB patients selected from a population of 97 through convenience sampling based on willingness to participate. Data on the relationship between family support (emotional, appraisal, informational, instrumental) and medication adherence were analyzed using the chi-square test. Medication adherence was very high (91.1%). No statistically significant relationship was found between overall family support and medication adherence (p = 1.000). However, sub-variable analysis revealed a sharp disparity: emotional (67% good) and appraisal (66% good) support were high, while informational (51% poor) and especially instrumental (97% poor) support were very low. In this highly adherent patient cohort, general family support was not a differentiating factor for adherence, however a critical deficit in informational and instrumental support was identified.